IMPLEMENTASI PROGRAM TRAINING OF TRAINER CABANG OLAHRAGA RUGBY DALAM MENINGKATKAN KOMPETENSI KEPELATIHAN PESERTA PELATIHAN OLAHRAGA - septi hariansyah (CV Abid Abadi Jaya, 2025)
The development of coaching competence is one of the important factors in supporting the success of sports development programs, including in rugby which requires strong physical ability, technical skills, and strategic gameplay. However, the limited number of coaches who possess adequate coaching competencies remains one of the challenges in the development of rugby at the regional level. Therefore, this community service activity aims to improve the coaching competence of participants through the implementation of a Training of Trainer (ToT) program in rugby. This community service activity was conducted in October 2025 at Jasdam Neusu Field, Banda Aceh, involving 24 participants consisting of rugby administrators from various districts and cities across Aceh Province. The implementation method was carried out through three main stages, namely preparation, implementation, and evaluation. The training activities included the delivery of sports coaching theory, demonstrations of basic rugby techniques, field practice, and coaching simulations. The evaluation of the activity was conducted using pre-test and post-test methods, as well as observations during practical sessions to measure the improvement of participants’ understanding and skills. The results showed that the Training of Trainer-based training program was able to enhance participants' understanding of the fundamental concepts of sports coaching and improve their skills in practicing basic rugby techniques. Therefore, this training activity can serve as an effective strategy to enhance coaching competence and support the development of rugby coaching programs in Aceh Province